Paciente em terapia nutricional enteral domiciliar: vídeo educativo sobre os cuidados e manutenção com a sonda enteral - Wada, Beatriz Fernandes (Universidade Federal de São Carlos, 2023)
Objective: construction of an educational video on the care and maintenance of the enteral tube aimed at family members and caregivers of patients undergoing Home Enteral Nutritional Therapy. Method: methodological study, developed in three phases: phase 1 saw the structuring of the script and storyboards of the video, in phase 2 the construction of the video was carried out and, in phase 3, the video was validated by professional judges and service users. Results: the video was created and validated by 8 professional judges and 8 patient care judges. As an agreement criterion, a minimum index of 0.80 was established for each item evaluated, as a result of which all items had a Content Validity Index of 1.0. The descriptive suggestions made by the judges were analyzed, and, when appropriate, they were changed in the video. Final conclusions: it is concluded that the educational video was prepared and validated, being suitable for dissemination and availability to caregivers. The publication of the educational video for caregivers or family members of patients will help strengthen health education and expand their knowledge and skills, which favors care and the provision of assistance, in addition to strengthening the professional and caregiver relationship.
Patient undergoing home enteral nutritional therapy: educational video on care and maintenance with the enteral tube
Keywords: Terapia nutricional; Nutrição enteral; Educação em saúde; Vídeo educativo; CIENCIAS DA SAUDE::ENFERMAGEM